The Concept of Ishlah in the Qur'an Surah Al-Hujurat Sayyid Qutb's Perspective in the Tafsir Fi Zhilalil-Qur’an - Hasibuan, Ahmad Yazid; Zuhri, Ahmad; Harahap, Mardian Idris (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
In living life, humans must be able to understand the Qur’an. For this reason, interpretation is needed from the ulama to explain in detail the meaning of the verses of the Qur'an, because people who do not receive guidance, guidance, and direction from Allah SWT are people who are at a loss. One aspect that is also important in society is ishlah. Allah SWT has decreed that fellow believers must be affectionate towards each other, and must not fight, let alone be enemies that lead to war. However, as time goes by, it cannot be denied that disputes can grow and occur, this is the location and function of the ishlah that Allah SWT has created. determine that all disputes no matter how big or small are resolved in a just and peaceful manner so that each conflicting party feels grateful and accepts wholeheartedly all the decisions that Allah SWT has made. assign to all humans. This research uses descriptive analytical methods so that readers can understand how Sayyid Qutb responds to the terms of Allah SWT, and assign it to society, especially to believers.